أساليب الهوية المميزة لطلبة بعض المراحل التعليمية في محافظة خان يونس - عبد الحميد النواجحة, زهير (Université de M'sila, 2017)
هدفت الدراسة الحالية التعرف إلى مستوى أساليب الهوية المميزة لدى الطلبة، والتحقق من الفروق في أساليب الهوية تبعاً لمتغير نوع المرحلة التعليمية (إعدادي، ثانوي، جامعي)، ووفقاً لمتغير الجنس، وتكونت عينة الدراسة من (306) طالب، وتم استخدام مقياس أساليب الهوية من إعداد بيرزونسكي، تعريب الباحث، وأظهرت نتائج الدراسة ارتفاع مستوى أسلوب الهوية الملتزم، ووجود فروق في الأسلوب المعلوماتي وأسلوب الالتزام والدرجة الكلية تبعاً لمتغير نوع المرحلة التعليمية لصالح المرحلة الجامعية، ووجود فروق في الأسلوب المعياري وفقاً لنوع المرحلة التعليمية لصالح طلبة الثانوية، من جانب آخر بينت النتائج عدم وجود فروق في الأسلوب المشتت- التجنبي وفقاً لنوع المرحلة التعليمية، كما أشارت النتائج إلى عدم وجود فروق بين الذكور والإناث في أساليب الهوية، باستثناء الأسلوب المشتت- التجنبي لصالح الإناث. The present study aimed to the level of identity styles distinctive among students, and Verification of differences in identity styles depending on the educational stage type (preparatory, secondary, university), and sex variable, The study sample consisted (306) students, The researcher used scale identity styles of preparation Berzonsky, The results showed a high level of identity style committed. The results showed a differences in informational style and commitment style and the total score. According to the type of educational stage for the Undergraduate Students. The existence of differences in the normative style according to type of educational stage in favor of secondary school students, While the results showed no differences in Diffuse-Avoidant Style according to the type of educational stage, also The results indicated no differences between males and females in the identity styles, except Diffuse-Avoidant Style in favor of females.
Keywords: أساليب الهوية.